Planowanie przestrzenne wobec interesu publicznego i prywatnego - Kieres, Leon (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The Constitutional Court considers area planning aconstitutional issue. Although it is not included in the regulations of the Constitution, area planning is, however, of particular importance for the country. Connections with the regulations of the Polish Constitution and the institutions included in it — eg. Ownership rights — determine the importance of area planning. The Constitutional Court points out, in its judgments, the situation of local government units in area planning. It indicates especially the boundaries of local government’s autonomy with regards to area planning.
Keywords: planowanie przestrzenne; interes publiczny; interes prywatny; Trybunał Konstytucyjny